Optimizing English learning in high schools with contemporary learning models using whiteboard animation - Sheila Agustina; Fika Megawati; Wahyu Taufiq; Nafi’ah Aghni Setyowati; Sevya Dwi Gita Nurani (Journal of Community Service and Empowerment, 2024)
Traditional approaches often fail to motivate students and cater to diverse learning styles, further compounded by the limited use of modern educational technologies. A community service program was implemented to address these issues, focusing on contemporary teaching models like the Happy Learning approach and the integration of whiteboard animation. This program explores the challenges high school English teachers face in Sidoarjo, Indonesia, concerning student engagement and effective teaching methods. Over one month, 47 high school English teachers participated in workshops and mentoring sessions designed to enhance their skills in these innovative methods. The results showed notable improvements in teachers' confidence and their ability to manage interactive classes. A significant majority found the contemporary models, including Happy Learning and whiteboard animation, to be effective, although some teachers still preferred traditional methods. Whiteboard animation was recognized for its role in clarifying content and engaging students, with many teachers successfully creating their media using various applications. Additionally, teachers preferred integrating game-based learning with whiteboard animation, indicating a shift towards more dynamic and student-centered teaching practices. This program underscores the effectiveness of combining modern teaching models with technology to improve educational outcomes and teacher effectiveness.